The role of kinin receptors in preventing neuroinflammation and its clinical severity during experimental autoimmune encephalomyelitis in mice. - Rafael C Dutra (Public Library of Science (PLoS), 2011)
Background Multiple sclerosis (MS) is a demyelinating and neuroinflammatory disease of the human central nervous system (CNS). The expression of kinins is increased in MS patients, but the underlying mechanisms by which the kinin receptor regulates MS development have not been elucidated. Methodology/principal findings Experimental autoimmune encephalomyelitis (EAE) was induced in female C57BL/6 mice by immunization with MOG(35-55) peptide emulsified in complete Freund's adjuvant and injected with pertussis toxin on day 0 and day 2. Here, we report that blockade of the B(1)R in the induction phase of EAE markedly suppressed its progression by interfering with the onset of the immune response. Furthermore, B(1)R antagonist suppressed the production/expression of antigen-specific T(H)1 and T(H)17 cytokines and transcription factors, both in the periphery and in the CNS. In the chronic phase of EAE, the blockade of B(1)R consistently impaired the clinical progression of EAE. Conversely, administration of the B(1)R agonist in the acute phase of EAE suppressed disease progression and inhibited the increase in permeability of the blood-brain barrier (BBB) and any further CNS inflammation. Of note, blockade of the B(2)R only showed a moderate impact on all of the studied parameters of EAE progression. Conclusions/significance Our results strongly suggest that kinin receptors, mainly the B(1)R subtype, play a dual role in EAE progression depending on the phase of treatment through the lymphocytes and glial cell-dependent pathways.